Prenatal Ultrasound Diagnosis of Klippel–Trenaunay Syndrome - Nicolae Gică; Andreea Dumitru; Anca Maria Panaitescu; Corina Gică; Gheorghe Peltecu; Anca Marina Ciobanu; Laura Bălănescu (Diagnostics, 2023)
Klippel–Trenaunay syndrome (KTS) is a very rare vascular malformation syndrome also referred to as a capillary–lymphatic–venous malformation with unknown aetiology. The aim of our paper is to highlight interesting images, regarding a rare case of foetal Klippel–Trenaunay syndrome diagnosed prenatally in our department and confirmed postnatally with a favourable evolution during the gestation and neonatal periods. This case was diagnosed at 26 weeks gestation and characterised through ultrasound by the presence of superficial multiple cystic structures of different sizes spreading over the left leg with hemihypertrophy and reduced mobility. The cystic lesions were spreading to the left buttock and the pelvic area. The right leg and upper limbs had normal appearance with good mobility. There were no signs of hyperdynamic circulation or foetal anaemia, but mild polyhydramnios was associated. The ultrasound findings were confirmed postnatally, the left leg presented multiple cystic lesions and port wine stains, and there was hypertrophy and fixed position, with favourable evolution at 6 months of life, when the size of the lesions began to decrease and the mobility of the leg improved.